Respuestas

2012-07-19T06:29:35+02:00

Suma de Polinomios:
P(x) = 2x3 + 5x - 3 Q(x) = 2x3 - 3x2 + 4x
P(x) + Q(x) = (2x3 + 5x - 3) + (2x3 -3x2 + 4x) 
P(x) + Q(x) = 2x3 + 2x3 - 3 x2 + 5x + 4x - 3
P(x) + Q(x) = 4x3- 3x2 + 9x - 3.
Resta de Polinomios:
P(x) − Q(x) = (2x3 + 5x - 3) − (2x3 - 3x2 + 4x) 
P(x) − Q(x) = 2x3 + 5x - 3 − 2x3 + 3x2 − 4x
P(x) − Q(x) = 2x3 − 2x3 + 3x2 + 5x− 4x - 3
P(x) − Q(x) = 3x2 + x - 3
Multiplicación de Polinomios:
P(x) = 2x2 - 3 Q(x) = 2x3 - 3x2 + 4x
P(x) · Q(x) = (2x2 - 3) · (2x3 - 3x2 + 4x) =